Institutional Management and Engagement with the Knowledge Society - Goddard, John (OECD Publishing, 2005)
The article will argue that external engagement with business and the community poses major challenges for the institutional management of Higher Education Institutions (HEIs). The world outside of academia, in business, central and local government, health, welfare and the cultural and community sectors increasingly expect an institutional as distinct from individual academic response to the challenges and opportunities for HEIs in their respective domains. Nowhere is this more apparent than at the city and regional scale where HEIs have the potential through their teaching and research to play a leading role in joining up the separate strands of development policy - such as innovation, skills, social inclusion - and providing a key link between the global and the local. But realising this external role requires strong institutional leadership and internal integration. The article addresses these issues by reference to policy and practice particularly in relation to knowledge exploitation in Finland and the United Kingdom